Airway M Cells Arise in the Lower Airway Due to RANKL Signaling and Reside in the Bronchiolar Epithelium Associated With iBALT in Murine Models of Respiratory Disease - Kimura, Shunsuke; Mutoh, Mami; Hisamoto, Meri; Saito, Hikaru; Takahashi, Shun; Asakura, Takanori; Ishii, Makoto; Nakamura, Yutaka; Iida, Junichiro; Hase, Koji; Iwanaga, Toshihiko (Frontiers in Immunology, 2019)
Microfold (M) cells residing in the follicle-associated epithelium of mucosa-associated lymphoid tissues are specialized for sampling luminal antigens to initiate mucosal immune responses. In the past decade, glycoprotein 2 (GP2) and Tnfaip2 were identified as reliable markers for M cells in the Peyer’s patches of the intestine. Furthermore, RANKL–RANK signaling, as well as the canonical and non-canonical NFκB pathways downstream, is essential for M-cell differentiation from the intestinal stem cells. However, the molecular characterization and differentiation mechanisms of M cells in the lower respiratory tract, where organized lymphoid tissues exist rarely, remain to be fully elucidated. Therefore, this study aimed to explore M cells in the lower respiratory tract in terms of their specific molecular markers, differentiation mechanism, and functions. Immunofluorescence analysis revealed a small number of M cells expressing GP2, Tnfaip2, and RANK is present in the lower respiratory tract of healthy mice. The intraperitoneal administration of RANKL in mice effectively induced M cells, which have a high capacity to take up luminal substrates, in the lower respiratory epithelium. The airway M cells associated with lymphoid follicles were frequently detected in the pathologically induced bronchus-associated lymphoid tissue (iBALT) in the murine models of autoimmune disease as well as pulmonary emphysema. These findings demonstrate that RANKL is a common inducer of M cells in the airway and digestive tracts and that M cells are associated with the respiratory disease. We also established a two-dimensional culture method for airway M cells from the tracheal epithelium in the presence of RANKL successfully. This model may be useful for functional studies of M cells in the sampling of antigens at airway mucosal surfaces.